Service Provider Difficulties in Operationalizing Coercive Control. (May 2019) - Brennan, Iain R.; Burton, Victoria; Gormally, Sinéad; O'Leary, Nicola
We examined perspectives of social workers, police officers, and specialist domestic abuse practitioners about their perceived ability and organizational readiness to respond effectively to incidents of coercive and controlling behavior. Interviews revealed intervention and risk assessment strategies structured around an outdated, maladaptive concept of domestic abuse as an unambiguous and violent event and frontline services that lacked appreciation of the power dynamics inherent in controlling relationships. The analysis demonstrates how lack of definitional clarity around nonphysical domestic abuse can increase the use of discretion by frontline services and, by extension, increase the discounting of coercive control by pressured frontline officers.